The effect of chronic yoga interventions on sleep quality in people with sleep disorders: a scoping review - Alghosi, Mohammad; Sharifi, Maryam; Namavari, Sanam; Rajamand, Neda; Bamorovat, Faezeh; Norouzi, Narges; Alimoradi, Mohammad; Konrad, Andreas (Frontiers in Neurology, 2025)
BackgroundPoor or insufficient sleep adversely affects various physiological and psychological functions, impacting body systems such as the endocrine, metabolic, and immune systems.ObjectivesDespite available pharmacological and non-pharmacological treatments, the impact of chronic yoga interventions on sleep quality in individuals with sleep problem syndrome remains underexplored. This scoping review aims to consolidate existing research on yoga interventions and their effects on sleep quality, providing evidence for yoga as a non-pharmacological alternative to reduce reliance on medications.MethodsA systematic search across PubMed, Web of Science, and Scopus identified 1,559 studies, with 57 meeting inclusion criteria for yoga’s effects on sleep quality.ResultsOverall, the included studies reported either significant improvements in sleep quality (or related) parameters or no change. Moderator analyses revealed that intervention duration and session frequency can influence sleep outcomes. Short-duration interventions (≤6 weeks) showed a large mean effect on sleep quality (9.41%; 95% CI 3.06 to 15.42%), with 54% of studies reporting statistically significant improvements. Medium-duration interventions (7–16 weeks) demonstrated consistent benefits, including a large mean effect on sleep quality (8.74%; 95% CI 2.93 to 14.55%) and a very large reduction in insomnia severity (13.19%; 95% CI 11.10 to 15.98%). However, sleep efficiency exhibited smaller effects (0.73%; 95% CI −1.99 to 3.45%). Long-duration interventions (≥17 weeks) produced the most robust results, with 100% of the studies reporting significant improvements, including a 7.92% increase in sleep quality (95% CI 3.23 to 12.60%). With regard to session frequency, low-frequency sessions (1–2 per week) yielded significant improvements in insomnia severity (13.66%; 95% CI 8.72 to 18.59%) and sleep quality (8.13%; 95% CI 2.67 to 13.59%). Moderate-frequency sessions (3–4 per week) balanced accessibility and efficacy, producing a large mean effect on sleep quality (9.21%; 95% CI 3.66 to 14.76%). High-frequency sessions (≥5 per week) demonstrated a similarly large effect on sleep quality (8.24%; 95% CI 2.28 to 14.20%), although the data were limited.ConclusionTailoring yoga interventions by duration and frequency is valuable, with chronic practice offering a safe, effective alternative to medication. Future research should refine protocols for specific populations and sleep challenges.